A palladium-catalyzed tandem reaction of 2-alkynylbenzenesulfonamides with 2-(2-bromoarylidene)cyclobutanones. Issue 6 (4th April 2016) - Gong, Xinxing; Xia, Hongguang; Wu, Jie
Abstract : The core of benzo[ f ][1, 2]thiazonin-5(4 H )-one 3, 3-dioxide is efficiently assembled through a palladium-catalyzed tandem reaction of 2-alkynylbenzenesulfonamides with 2-(2-bromobenzylidene)cyclobutanones via double carbometallation. A range of polycycles with a nine-membered sultam ring are generated in moderate to good yields. Abstract : The core of benzo[ f ][1, 2]thiazonin-5(4 H )-one 3, 3-dioxide is efficiently assembled through a palladium-catalyzed tandem reaction of 2-alkynylbenzenesulfonamides with 2-(2-bromobenzylidene)cyclobutanones. A range of polycycles with a nine-membered sultam ring are generated in moderate to good yields. During the transformation, three new bonds are formed via a tandem process with the construction of a nine-membered sultam ring. Double carbometallation is believed to be involved with the ring-opening of cyclobutanone.